A Lightweight Haptic Interface for Hand-to-Object Tasks With Spatiotemporal Displays - Fang, Yun; Guo, Weichao; Chai, Guohong; Sheng, Xinjun (IEEE transactions on industrial electronics (1982), 2024)
Haptic interfaces create information transmission channels from machine to human with a natural way. Robust haptic interfaces with compact forms that provide high information throughput are of particular interest in industrial applications such as teleoperation, soft displays, virtual, and augmented reality. Here, we propose a haptic interface with spatiotemporal displays to convey high-dimensional information during successive hand-to-object tasks, which is architectural and psychophysical lightweight. The wearable and flexible architecture incorporates seven independently addressable vibration units at a pitch of 16 mm to allow spatiotemporal modulation. To prove the superiority of the haptic interface, four-day perceptual experiments are performed on 12 subjects with pattern discrimination tasks. We compared recognition accuracy (RA) between space-dependent and spatiotemporal strategies across the forearm, which are encoded based on finger states and morphological deformations. Furthermore, the mixed biomimetic strategy derived from both is intuitive and showed strength in terms of RA (over 88%) and information transfer (IT) (over 2.4 bit/s). With prior knowledge, are significantly better (RA over 90%) at the discrimination of sequential patterns. Moreover, the results demonstrate robust performance of the biomimetic strategy on location shift, which prove that subjects perceive relative information among vibratory units rather than absolute locations on the skin.